The Influence of Tax Avoidance, Cash Flow Operations, Firm Size and Return on Assets on the Cost of Debt in Coal Mining Companies in Indonesia - Kamila, Nurul; Moelyo Adhi, Triyogo; Saputro Aji, Ditya (Journal of Business and Behavioural Entrepreneurship, 2023)
This research is intended to reveal the effect of tax avoidance, operational cash flow, company size and Return on Assets (ROA) to the cost of debt in coal mining sector companies listed on the Indonesia Stock Exchange during the period 2017 to 2022. Multiple regression analysis as a statistical test is applied in this research. The findings from this research are evidence that tax avoidance, cash flow operations, company size and ROA have an effect on the cost of debt. From this evidence, tax avoidance and ROA have a positive direction, while cash flow operations and company size have a negative direction towards the cost of debt.